Body iron stores and heme-iron intake in relation to risk of type 2 diabetes: a systematic review and meta-analysis. - Zhuoxian Zhao; Sheyu Li; Guanjian Liu; Fangfang Yan; Xuelei Ma; Zeyu Huang; Haoming Tian (PLoS ONE)
Background and objective Emerging evidence from biological and epidemiological studies has suggested that body iron stores and heme-iron intake may be related to the risk of type 2 diabetes (T2D). We aimed to examine the association of body iron stores and heme-iron intake with T2D risk by conducting a systematic review and meta-analysis of previously published studies. Research design and methods Systematic review and subsequent meta-analysis were conducted by searching MEDLINE database up to June 22, 2012 to identify studies that analyzed the association of body iron stores or dietary heme-iron intake with T2D risk. The meta-analysis was performed using the effect estimates and 95% confidence intervals (CIs) to calculate the pooled risk estimates, while the heterogeneity among studies was examined using the I(2) and Q statistic. Results The meta-analysis included 16 high-quality studies: 12 studies analyzed ferritin levels (4,366 T2D patients and 41,091 controls) and 4 measured heme-iron intake (9,246 T2D patients and 179,689 controls). The combined relative risk (RR) comparing the highest and lowest category of ferritin levels was 1.66 (95% CI: 1.15-2.39) for prospective studies, 2.29 (95% CI: 1.48-3.54) for cross-sectional studies with heterogeneity (Q = 14.84, p = 0.01, I(2) = 66.3%; Q = 44.16, p<0.001, I(2) = 88.7%). The combined RR comparing the highest and lowest category of heme-iron intake was 1.31 (95% CI: 1.21-1.43) with heterogeneity (Q = 1.39, p = 0.71, I(2) = 0%). No publication bias was found. Additional 15 studies that were of good quality, had significant results, and analyzed the association between body iron stores and T2D risk were qualitatively included in the systematic review. Conclusions The meta-analysis and systematic review suggest that increased ferritin levels and heme-iron intake are both associated with higher risk of T2D.